2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32559
|View full text |Cite
|
Sign up to set email alerts
|

Creating Environments for Critical Thinking: Building Upon Multiple Choice Problems in Electrical Engineering Education

Abstract: is interested in scholarly teaching and uses active learning techniques to help students achieve expert-like level of thinking. She guides students in bridging the gap between facts and usable knowledge to solve complex engineering problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The results of structural equation analysis indicated that the autonomy supportive environment was a significant predictor of critical thinking. This finding is consistent with previous research on the impact of learning environments on critical thinking (Kanadli, 2019;Baghdadchi et al, 2019;Wan and Cheng, 2018;Tironeh et al, 2017;Radulovic & Stancic, 2017;Marin & Halpern, 2011). autonomy supportive environment encourages learners to be able to examine learning situations from different aspects, such as how to do homework and select educational topics, and provides this possibility for them.…”
Section: Discussionsupporting
confidence: 92%
“…The results of structural equation analysis indicated that the autonomy supportive environment was a significant predictor of critical thinking. This finding is consistent with previous research on the impact of learning environments on critical thinking (Kanadli, 2019;Baghdadchi et al, 2019;Wan and Cheng, 2018;Tironeh et al, 2017;Radulovic & Stancic, 2017;Marin & Halpern, 2011). autonomy supportive environment encourages learners to be able to examine learning situations from different aspects, such as how to do homework and select educational topics, and provides this possibility for them.…”
Section: Discussionsupporting
confidence: 92%
“…One study even showed that open book and open web exams better engage students, minimize the desire to cheat, and can yield better student learning . Take home exams also provide students an opportunity to apply their knowledge in meaningful, authentic situations, which helps stimulate critical thinking. ,, Students are able to focus on the question asked, especially since the questions require higher-order thinking and synthesis of knowledge.…”
Section: Assessment Strategiesmentioning
confidence: 99%
“…27 Take home exams also provide students an opportunity to apply their knowledge in meaningful, authentic situations, which helps stimulate critical thinking. 27,29,30 Students are able to focus on the question asked, especially since the questions require higher-order thinking and synthesis of knowledge.…”
Section: ■ Assessment Strategiesmentioning
confidence: 99%
“…The multiple-choice quiz was selected as the method for the continuous assessment for various reasons. Firstly, using multiple-choice questions in assessment is common in engineering education [6,7]. The method must be steered to promote learning and match the course learning outcomes.…”
Section: Description Of the Coursementioning
confidence: 99%